A AKIBAT PUTUSNYA PERKAWINAN CAMPURAN BERIMPLIKASI TERHADAP HAK ASUH ANAK PERSPEKTIF HUKUM PERDATA INTERNASIONAL : Indoneisa - padang, rasshidiq wahid (Universitas Kapuas, 2024)
As a result of the breakdown of marriages raises significant concerns regarding child custody within the framework of Private International Law. The primary challenge lies in determining child custody when partners from different countries are involved. Offspring of mixed marriages often possess dual or restricted citizenship based on the laws of each parent's respective country. However, the conclusion of the marriage prompts questions about how child custody is to be established and how it is influenced by the legal systems of each parent's nation. This research aims to address the issue of child custody in mixed marriages from an international civil law perspective. To achieve this, a qualitative approach, incorporating a literature review and legislative analysis, will be employed. The study will draw on scientific sources, including articles and academic works, as well as data from national laws in Indonesia, the Convention on the Rights of the Child, and relevant international laws governing rights in this context. Given the increasing prevalence of mixed marriages in Indonesia due to the effects of globalization, this research will focus on the repercussions of divorce in such marriages. Specifically, it will delve into the challenges surrounding the custody of children, emphasizing how the jurisdiction where the divorce is filed dictates the legal framework for defending and adjudicating child custody. The study will also explore issues such as proving a child's legitimacy as a biological offspring, determining the rightful custodian, addressing financial responsibilities for child maintenance and education post-custody resolution, and establishing arrangements for the child's citizenship.